Kajian Pemanfaatan Ruang Kota Berkelanjutan (Studi Kasus di Kota Denpasar) - Wiryananda, Ngakan Gd. A. Khrisna; Hasibuan, Hayati Sari; Madiasworo, Taufan (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2018)
Abstract: The rapid development of tourism and the population growth of the population caused the problem on the spatial utilization of Denpasar City. The spatial utilization that occurred has not been in accordance with the objectives to be achieved. The fact is that the economy continues to grow, but ignores the existing environmental aspects. This study aims to analyzethe impact of spatial utilization on environmental and economic aspects as well as to formulate the sustainable urbanspatial utilization. This research uses spatial analysis technique and calculate sustainability index of environmental and economic. The results show that during the period of 2011 to 2015 the land use for settlements, tourism, and rice fields is not in accordancewith the spatial plan of Denpasar City 2011-2031. The impact of spatial utilization on environmental and economical aspects leads to unsustainable. This is evident from the environmental index value of the year 2011 that is 1.065 continues to decline to 1.056 in 2015. The economic index value which tends to decrease that is 1.012 in 2011 down to 0.992 in 2015. The formulation of sustainable urban spatial utilization should be done by planning the vertical building, implementation of autonomous traditionalrules, the implementation of perennial rice field, the utilization of vacant land and establishment of task control unit of traditional village.Â Abstrak:Pesatnya perkembangan pariwisata dan pertumbuhan penduduk menyebabkan permasalahan pada pemanfaatan ruang Kota Denpasar. Pemanfaatan ruang yang terjadi belum sesuai dengan tujuan yang ingin dicapai. Fakta yang terjadi yaitu perekonomian terus mengalami pertumbuhan, namun mengabaikan aspek lingkungan yang ada. Penelitian ini bertujuan untuk menganalisis dampak pemanfaatan ruang pada aspek lingkungan dan ekonomi serta merumuskan pemanfaatan ruang Kota Denspasar yang berkelanjutan. Penelitian ini menggunakan teknik analisis spasial dan menghitung indeks keberlanjutan lingkungan dan ekonomi. Hasil penelitian menunjukkan selama kurun waktu 2011 sampai 2015 penggunaan lahan untuk pemukiman, pariwisata, dan sawah belum sesuai dengan RTRW Kota Denpasar 2011-2031. Dampak pemanfaatan ruang pada aspek lingkungan dan ekonomi mengarah pada tidak berkelanjutan. Hal tersebut terlihat dari nilai indeks lingkungan tahun 2011 yaitu 1,065 terus menurun menjadi 1,056 pada 2015. Nilai indeks ekonomi cenderung mengalami penurunan yaitu 1,012 tahun 2011 menjadi 0,992 tahun 2015. Rumusan pemanfaatan ruang kota berkelanjutan dilakukan dengan merencanakan bangunan vertikal, penerapan aturan adat secara otonom, penerapan sawah abadi, pemanfaatan lahan kosong dan pembentukan satuantugas pengendalian ruang adat.